Process Safety Risk Analysis of a Secondary Reformer in an Ammonia Production Industry - Parapat , Riny Yolandha; Fitri, Sulistya Nurul; Astuti, Santi Puji (Jurnal Penelitian Inovatif, 2026)
Ammonia production is one of the most important processes in the chemical industry and involves several interconnected units operating under high-temperature and high-pressure conditions. Among these units, the secondary reformer plays a critical role in completing methane conversion and supplying nitrogen required for ammonia synthesis. Due to the presence of flammable gases, elevated operating temperatures exceeding 900°C, and highly exothermic reactions, the secondary reformer presents significant process safety challenges that require systematic hazard identification and risk assessment. This study aims to analyze process safety risks associated with the secondary reformer unit in an ammonia production plant using the Hazard and Operability Study (HAZOP) method. The analysis was conducted through field observations, interviews with operating personnel, and evaluation of Process Flow Diagrams (PFD) and Piping and Instrumentation Diagrams (P&ID). Key process parameters, including temperature, pressure, flow rate, and gas composition, were systematically assessed to identify potential deviations, determine their causes and consequences, evaluate existing safeguards, and propose risk mitigation measures. The results identified 17 potential process deviations with risk scores ranging from 2 to 10. The highest-risk deviations were associated with overheating and excessive combustion in the combustion zone, as well as gas leakage and overpressure in the reactor shell and pressure control system. These deviations may result in refractory damage, catalyst deterioration, thermal runaway, fire, explosion, and loss of containment. Existing safeguards, including temperature and pressure monitoring systems, gas detectors, alarms, pressure safety valves, and interlock systems, were found to significantly reduce risk levels. The findings demonstrate that HAZOP is an effective tool for identifying process hazards and prioritizing mitigation measures, thereby improving process safety and operational reliability in ammonia production facilities.